Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Certainly! Let's break down the problem step-by-step to find the required solutions and coordinates.
### Step 1: Solutions of the Equation [tex]\(2x^2 = -x^2 - 5x - 1\)[/tex]
First, let's solve the equation [tex]\(2x^2 = -x^2 - 5x - 1\)[/tex]. Rearranging all terms to one side gives us:
[tex]\[ 2x^2 + x^2 + 5x + 1 = 0 \][/tex]
[tex]\[ 3x^2 + 5x + 1 = 0 \][/tex]
We solve the quadratic equation [tex]\(3x^2 + 5x + 1 = 0\)[/tex]. The solutions for [tex]\(x\)[/tex] are:
[tex]\[ x = -\frac{5}{6} - \frac{\sqrt{13}}{6} \][/tex]
[tex]\[ x = -\frac{5}{6} + \frac{\sqrt{13}}{6} \][/tex]
### Step 2: [tex]\(y\)[/tex]-Coordinates of the Intersection Points
Next, we need the [tex]\(y\)[/tex]-coordinates of the intersection points of the graphs [tex]\(y = 2x^2\)[/tex] and [tex]\(y = -x^2 - 5x - 1\)[/tex]. We substitute the [tex]\(x\)[/tex]-values found from the solutions into [tex]\(y = 2x^2\)[/tex]:
For [tex]\(x = -\frac{5}{6} - \frac{\sqrt{13}}{6}\)[/tex]:
[tex]\[ y = 2 \left( -\frac{5}{6} - \frac{\sqrt{13}}{6} \right)^2 \][/tex]
For [tex]\(x = -\frac{5}{6} + \frac{\sqrt{13}}{6} \)[/tex]:
[tex]\[ y = 2 \left( -\frac{5}{6} + \frac{\sqrt{13}}{6} \right)^2 \][/tex]
### Step 3: [tex]\(x\)[/tex]-Coordinates of the [tex]\(x\)[/tex]-Intercepts
Now, let's find the [tex]\(x\)[/tex]-coordinates of the [tex]\(x\)[/tex]-intercepts for the graphs [tex]\(y = 2x^2\)[/tex] and [tex]\(y = -x^2 - 5x - 1\)[/tex]:
For [tex]\(y = 2x^2\)[/tex]:
[tex]\[ 2x^2 = 0 \][/tex]
[tex]\[ x = 0 \][/tex]
For [tex]\(y = -x^2 - 5x - 1\)[/tex], we solve:
[tex]\[ -x^2 - 5x - 1 = 0 \][/tex]
The solutions for [tex]\(x\)[/tex] are:
[tex]\[ x = -\frac{5}{2} - \frac{\sqrt{21}}{2} \][/tex]
[tex]\[ x = -\frac{5}{2} + \frac{\sqrt{21}}{2} \][/tex]
### Step 4: [tex]\(y\)[/tex]-Coordinates of the [tex]\(y\)[/tex]-Intercepts
Finally, we find the [tex]\(y\)[/tex]-coordinates of the [tex]\(y\)[/tex]-intercepts for the graphs [tex]\(y = 2x^2\)[/tex] and [tex]\(y = -x^2 - 5x - 1\)[/tex]:
For [tex]\(y = 2x^2\)[/tex], setting [tex]\(x = 0\)[/tex]:
[tex]\[ y = 2 \cdot 0^2 = 0 \][/tex]
For [tex]\(y = -x^2 - 5x - 1\)[/tex], setting [tex]\(x = 0\)[/tex]:
[tex]\[ y = -0^2 - 5\cdot0 - 1 = -1 \][/tex]
### Summary of Results
1. Solutions of the equation [tex]\(2x^2 = -x^2 - 5x - 1\)[/tex]:
[tex]\[ x = -\frac{5}{6} - \frac{\sqrt{13}}{6}, \quad x = -\frac{5}{6} + \frac{\sqrt{13}}{6} \][/tex]
2. [tex]\(y\)[/tex]-coordinates of the intersections points of [tex]\(y=2x^2\)[/tex] and [tex]\(y=-x^2-5x-1\)[/tex]:
[tex]\[ y = 2 \left( -\frac{5}{6} - \frac{\sqrt{13}}{6} \right)^2, \quad y = 2 \left( -\frac{5}{6} + \frac{\sqrt{13}}{6} \right)^2 \][/tex]
3. [tex]\(x\)[/tex]-coordinates of the [tex]\(x\)[/tex]-intercepts of [tex]\(y=2x^2\)[/tex] and [tex]\(y=-x^2-5x-1\)[/tex]:
[tex]\[ x = 0, \quad x = -\frac{5}{2} - \frac{\sqrt{21}}{2}, \quad x = -\frac{5}{2} + \frac{\sqrt{21}}{2} \][/tex]
4. [tex]\(y\)[/tex]-coordinates of the [tex]\(y\)[/tex]-intercepts of [tex]\(y=2x^2\)[/tex] and [tex]\(y=-x^2-5x-1\)[/tex]:
[tex]\[ y = 0, \quad y = -1 \][/tex]
### Step 1: Solutions of the Equation [tex]\(2x^2 = -x^2 - 5x - 1\)[/tex]
First, let's solve the equation [tex]\(2x^2 = -x^2 - 5x - 1\)[/tex]. Rearranging all terms to one side gives us:
[tex]\[ 2x^2 + x^2 + 5x + 1 = 0 \][/tex]
[tex]\[ 3x^2 + 5x + 1 = 0 \][/tex]
We solve the quadratic equation [tex]\(3x^2 + 5x + 1 = 0\)[/tex]. The solutions for [tex]\(x\)[/tex] are:
[tex]\[ x = -\frac{5}{6} - \frac{\sqrt{13}}{6} \][/tex]
[tex]\[ x = -\frac{5}{6} + \frac{\sqrt{13}}{6} \][/tex]
### Step 2: [tex]\(y\)[/tex]-Coordinates of the Intersection Points
Next, we need the [tex]\(y\)[/tex]-coordinates of the intersection points of the graphs [tex]\(y = 2x^2\)[/tex] and [tex]\(y = -x^2 - 5x - 1\)[/tex]. We substitute the [tex]\(x\)[/tex]-values found from the solutions into [tex]\(y = 2x^2\)[/tex]:
For [tex]\(x = -\frac{5}{6} - \frac{\sqrt{13}}{6}\)[/tex]:
[tex]\[ y = 2 \left( -\frac{5}{6} - \frac{\sqrt{13}}{6} \right)^2 \][/tex]
For [tex]\(x = -\frac{5}{6} + \frac{\sqrt{13}}{6} \)[/tex]:
[tex]\[ y = 2 \left( -\frac{5}{6} + \frac{\sqrt{13}}{6} \right)^2 \][/tex]
### Step 3: [tex]\(x\)[/tex]-Coordinates of the [tex]\(x\)[/tex]-Intercepts
Now, let's find the [tex]\(x\)[/tex]-coordinates of the [tex]\(x\)[/tex]-intercepts for the graphs [tex]\(y = 2x^2\)[/tex] and [tex]\(y = -x^2 - 5x - 1\)[/tex]:
For [tex]\(y = 2x^2\)[/tex]:
[tex]\[ 2x^2 = 0 \][/tex]
[tex]\[ x = 0 \][/tex]
For [tex]\(y = -x^2 - 5x - 1\)[/tex], we solve:
[tex]\[ -x^2 - 5x - 1 = 0 \][/tex]
The solutions for [tex]\(x\)[/tex] are:
[tex]\[ x = -\frac{5}{2} - \frac{\sqrt{21}}{2} \][/tex]
[tex]\[ x = -\frac{5}{2} + \frac{\sqrt{21}}{2} \][/tex]
### Step 4: [tex]\(y\)[/tex]-Coordinates of the [tex]\(y\)[/tex]-Intercepts
Finally, we find the [tex]\(y\)[/tex]-coordinates of the [tex]\(y\)[/tex]-intercepts for the graphs [tex]\(y = 2x^2\)[/tex] and [tex]\(y = -x^2 - 5x - 1\)[/tex]:
For [tex]\(y = 2x^2\)[/tex], setting [tex]\(x = 0\)[/tex]:
[tex]\[ y = 2 \cdot 0^2 = 0 \][/tex]
For [tex]\(y = -x^2 - 5x - 1\)[/tex], setting [tex]\(x = 0\)[/tex]:
[tex]\[ y = -0^2 - 5\cdot0 - 1 = -1 \][/tex]
### Summary of Results
1. Solutions of the equation [tex]\(2x^2 = -x^2 - 5x - 1\)[/tex]:
[tex]\[ x = -\frac{5}{6} - \frac{\sqrt{13}}{6}, \quad x = -\frac{5}{6} + \frac{\sqrt{13}}{6} \][/tex]
2. [tex]\(y\)[/tex]-coordinates of the intersections points of [tex]\(y=2x^2\)[/tex] and [tex]\(y=-x^2-5x-1\)[/tex]:
[tex]\[ y = 2 \left( -\frac{5}{6} - \frac{\sqrt{13}}{6} \right)^2, \quad y = 2 \left( -\frac{5}{6} + \frac{\sqrt{13}}{6} \right)^2 \][/tex]
3. [tex]\(x\)[/tex]-coordinates of the [tex]\(x\)[/tex]-intercepts of [tex]\(y=2x^2\)[/tex] and [tex]\(y=-x^2-5x-1\)[/tex]:
[tex]\[ x = 0, \quad x = -\frac{5}{2} - \frac{\sqrt{21}}{2}, \quad x = -\frac{5}{2} + \frac{\sqrt{21}}{2} \][/tex]
4. [tex]\(y\)[/tex]-coordinates of the [tex]\(y\)[/tex]-intercepts of [tex]\(y=2x^2\)[/tex] and [tex]\(y=-x^2-5x-1\)[/tex]:
[tex]\[ y = 0, \quad y = -1 \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.